Implementation of Freedom Mini Curriculum in Basic English at Tri Learning House - -, Tri Andayani; Siti Aisyah (Universitas Nahdatul Ulama Surabaya, 2024)
Execution of the independent curriculum necessitates that educators at Tri Learning House swiftly grasp and proficiently adapt to its requirements. This study explores the implementation process of an autonomous English curriculum, encompassing the stages of planning, execution, and evaluation. Employing a qualitative field study methodology, data was collected through methods such as observation, interviews, and document analysis. The study subjects included the owner of Tri Learning House, English teachers, and students. Data analysis techniques involved data reduction, presentation, and reaching conclusions. Findings revealed the successful integration of the independent English curriculum, which involved meticulous planning and managing in Tri learning House course implementation of ATP and teaching modules aligned with the Ministry of Education and Culture learning objectives. Additionally, various assessments, including summative, formative, and Project-Based Learning (PBL) assessments, were employed to measure student progress and understanding. Keywords: Implementation, freedom mini curriculum, Tri Learning House